Health by Design: Interweaving Health Promotion into Environments and Settings - Springer, Andrew E.; Evans, Alexandra E.; Ortuño, Jaquelin; Salvo, Deborah; Varela Arévalo, Maria Teresa (Frontiers in Public Health, 2017)
The important influence of the environmental context on health and health behavior– which includes place, settings and the multiple environments within place and settings - has directed health promotion planners from a focus solely on changing individuals, toward a focus on harnessing and changing context for individual and community health promotion. Health promotion planning frameworks such as Intervention Mapping provide helpful guidance in addressing various facets of the environmental context in health intervention design, including the environmental factors that influence a given health condition or behavior, environmental agents who can influence a population’s health, and environmental change methods. In further exploring how to harness the environmental context for health promotion, we examine in this paper the concept of interweaving of health promotion into context, defined as weaving or blending together health promotion strategies, practices, programs and policies to fit within, complement, and build from existing settings and environments. Health promotion interweaving stems from current perspectives in health intervention planning, improvement science and complex systems thinking by guiding practitioners from a conceptualization of context as a backdrop to intervention, to one that recognizes context as integral to the intervention design and to the potential to directly influence health outcomes. In exploring the general approach of health promotion interweaving, we examine selected theoretical and practice-based interweaving concepts in relation to four key environments (the policy environment, the information environment, the social/cultural/ organizational environment, and the physical environment), followed by evidence-based and practice-based examples of health promotion interweaving from the literature. Interweaving of health promotion into context is a common practice for health planners in designing health promotion interventions, yet one which merits further intentionality as a specific health promotion planning design approach.